PERBEDAAN GENDER TERHADAP PRESTASI BELAJAR SISWA SMAN 5 MADIUN - Rakita Sari; Rianti Ningsih; St. Muwwadah (FIPA : Forum Ilmiah Pendidikan Akuntansi, 2013)
This study aims to examine gender differences on student achievement SMAN 5 Madiun class X3, X6, X8 on economic subjects. Total sample of 100 students consist of 34 male students and 66 female students. The hypothesis tested in this study using the Independent samples ttest with Levene's test was done previously (homogeneity test). the results of this study indicate that there is no significant difference between female students and male students on learning achievement at grade economics X3, X6, X8.